Comparative study of two Lotus species: Phytochemistry, cytotoxicity and antioxidant capacity - Ahmed M. M. Youssef; Zeinb A. S. EL-Swaify; Doaa A. M. Maaty; Mohamed M. Youssef (GarVal Editorial Ltda., 2020)
Context: Phenolic and flavonoid compounds present in Lotus arabicus and L. glaber have not been identified yet. Also, no reports are demonstrating the cytotoxic and antioxidant activities of both lotus species. Therefore, it is interesting to study the anticancer effects and antioxidant capacity of them. Aims: To identify and evaluate the potential cytotoxic and antioxidant activities of phenolic and flavonoid compounds of methanol extracts of two Lotus species. Methods: High-Performance Liquid Chromatography (HPLC) was used to identify and quantify the potential compounds of the methanol extracts of both Lotus species. The cytotoxic activity of each methanol extract of the Lotus arabicus and L. glaber was investigated against seven cancer cell lines and one normal cell line. The cell viability was quantitated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, and the half-maximal inhibitory concentration (IC50) was estimated and compared with doxorubicin. Moreover, the antioxidant capacity of them was evaluated by 2, 2-diphenyl-1-picryl-hydrazyl-hydrate (DPHH) assay, and the scavenging percentage was calculated and compared with ascorbic acid. Results: The identified and quantitated phenolic compounds of the methanol extracts of both Lotus species were 17 phenolic acids and 16 flavonoids. The results showed that the active constituents of L. arabicus had cytotoxic activities against prostate cancer (IC50 = 401 ± 5 µg/mL), colon cancer (IC50 = 511 ± 181 µg/mL) and breast cancer (IC50 = 978 ± 54 µg/mL) greater than L. glaber which showed cytotoxic activities against prostate cancer (IC50 = 5094 ± 531 µg/mL), colon cancer (IC50 = 6522 ± 272 µg/mL) and breast cancer (IC50 = 2964 ± 404 µg/mL) in comparison with doxorubicin. Conclusions: L. arabicus may have active constituents that could be used for the treatment of prostate, colon or lung cancer. Therefore, isolation of phenolic and flavonoid compounds exist in L. arabicus may be required in the future.